1978
DOI: 10.4319/lo.1978.23.6.1089
|View full text |Cite
|
Sign up to set email alerts
|

Combat between predatory copepods and their prey: Cyclops, Epischura, and Bosmina1

Abstract: Predatory copepods are not imprecise hunters: they are capable of sophisticated behavior. Pelagic species (Cyclops, Epischura) usually sense approaching prey from a distance and must judge approach angle and prey speed, reorient during attack, and often vary their handling responses. Below certain crucial sizes that trigger avoidance responses in the predator, attack distances are related to prey size and speed. Cyclopoids and predatory calanoids (Epischwa) capture and handle prey differently, and the morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
137
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(141 citation statements)
references
References 14 publications
3
137
0
Order By: Relevance
“…M. albidus was a more efficient predator of younger than of older larvae. M. aspericornis consumed about 33 to 50 first instar larvae of Ae. aegypti within 24 h period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M. albidus was a more efficient predator of younger than of older larvae. M. aspericornis consumed about 33 to 50 first instar larvae of Ae. aegypti within 24 h period.…”
Section: Discussionmentioning
confidence: 99%
“…Swimming behaviour, as well as size, has been shown to influence predation success in copepods [33,34] . These studies reported that copepod species preyed mainly on early instar larvae of mosquito and almost null predatory capacity upon older larvae was not surprising, considered that copepod cyclopoids are generally not large enough to kill third and fourth instar mosquito larvae.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti larvae by M. annulatus resulting in the differential predation observed. Previous studies have shown 1st instar mosquito density the importance of morphological and behavioral characteristics other than prey size as defense mechanisms from predation by cyclopoids (Kerfoot 1978, Williamson 1983.…”
Section: Mortalitymentioning
confidence: 97%
“…Visual conspicuousness in prey body size, shape, pigmentation, and motion can all influence the selection by planktivorous fish (O'Brien 1979). Many invertebrate predators, such as Calanoid and cyclopoid copepods, insect larvae, and chaetognaths, use sensory setae to detect the hydrodynamic disturbances produced by the swimming motions of their zooplankton prey (Horridge and Boulton 1967;Strickler andBal1973;Strickler 1975;Kerfoot 1978). Prey selection by mechanosensory invertebrate predators is thus influenced by the hydrodynamic conspicuousness of their prey.…”
mentioning
confidence: 99%